PENGUATAN KAPASITAS MANAJEMEN KELEMBAGAAN KOPERASI PADA KOPERASI WEAR MANUN MAJU DI OHOI EVU KABUPATEN MALUKU TENGGARA - Saiful, Saiful; Ruban, Angela (Pattimura University, 2022)
The potential of marine and fishery resources owned by Indonesia is considered capable of supporting fish trading businesses with high economic value. One of the groups that run a marine and fisheries business is the Wear Manun Maju Joint Business Cooperative (KUB) which is located in Ohoi Village, Southeast Maluku. The potential of fisheries resources is quite abundant, including the potential of crabs in Ohoi Village, Southeast Maluku. Crab which is a potential resource is one of the goals of fishermen in the area, especially KUB Wear Manun Maju fishermen. The target of this outreach activity is to increase the institutional management capacity of the Wear Manun Maju cooperative. The extension method is carried out by the lecture and discussion method. Providing information to the KUB Wear Manun Maju cooperative regarding cooperative institutional management carried out through community service activities is expected to assist the management and members in developing cooperatives according to their respective duties and responsibilities and business planning in cooperatives so that every activity carried out can be directed towards welfare. its members